2016
DOI: 10.1186/s13072-016-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of the CENP-A chromatin domain is spatially and temporally constrained at human centromeres

Abstract: BackgroundChromatin containing the histone variant CENP-A (CEN chromatin) exists as an essential domain at every centromere and heritably marks the location of kinetochore assembly. The size of the CEN chromatin domain on alpha satellite DNA in humans has been shown to vary according to underlying array size. However, the average amount of CENP-A reported at human centromeres is largely consistent, implying the genomic extent of CENP-A chromatin domains more likely reflects variations in the number of CENP-A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…CENP-A nucleosomes appear to spread only far enough to create a centromeric chromatin domain that will confer chromosome stability. It appears that once the centromeric chromatin domain was established on the del(17), it has remained largely static, suggesting that centromere formation on non-centromeric sequences follows similar rules of inheritance at endogenous centromeres (Ross et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CENP-A nucleosomes appear to spread only far enough to create a centromeric chromatin domain that will confer chromosome stability. It appears that once the centromeric chromatin domain was established on the del(17), it has remained largely static, suggesting that centromere formation on non-centromeric sequences follows similar rules of inheritance at endogenous centromeres (Ross et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The molecular sizes of D17Z1 in L65-14A (3.7Mb) and L65-13A (0.7 Mb) had been previously calculated (Wevrick et al, 1990) and re-confirmed in our lab (Aldrup-MacDonald et al, in press ). Cenp-A domain size was calculated from the ratio of the length of Cenp-A antibody signal over the length of the D17Z1 array signal (Sullivan et al, 2011, Ross et al, 2016)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the centromere formed at a given variant D17Z1 array might reflect several of these organizational scenarios. We recently showed that CENPA chromatin is assembled and maintained at the same general region of alpha satellite DNA (Ross et al 2016), so a key question is if D17Z1 array variation disrupts the largely static placement of centromeric chromatin on HSA17.…”
Section: Genomic Variation Affects Centromere Functionmentioning
confidence: 99%
“…The location of the centromere is highly fixed on the chromosome, with new CENP-A nucleosomes assembled near the domain of existing CENP-A [45]. The selective deposition of new CENP-A at the existing centromere is achieved by coupling the proteins required for CENP-A deposition to CCAN proteins, including CENP-A itself.…”
Section: Cell Cycle Control Of Centromere Inheritancementioning
confidence: 99%